CALIFORNIA AND THE MAKING OF MODERN SPORT. - FRANKS, JOEL S. (Routledge research in sports history, 2025)
This book examines the importance of California - a socio-cultural, economic and political powerhouse - in the history of modern sport. It argues that California has had a profound influence, for better or worse, on the way that not only America but also the wider world plays sport and spends money to watch others play.The book traces the history of sport in California from the mid-nineteenth century to the present, and looks at how the state's historical development, its climate, and its unique racial and ethnic demographics have influenced sport at the elite level and in the wider community. It considers the importance of spatial politics and cultural citizenship in the development of Californian sport, and tells the story of how franchises such as the 49ers and the Lakers, as well as individual athletes such as Jackie Robinson and Billie Jean King have had a profound influence on the way their sports have been consumed, across America and in the wider world. The book also takes a close look at the impact of mega-sporting events in the Californian story, providing historical context for the LA 2028 Olympic Games and tracing the full arc of the 'Californization' of modern sports.This is fascinating reading for anybody with an interest in sport history, American history, social and cultural history, or the relationship between sport and wider society.